Ushul Fikih Sebagai Landasan Dinamis Pemikiran Hukum Islam - Hasir Budiman Ritonga (PT Anugerah Literasi Indomedia, 2026)
Ushul fiqh is a discipline that functions as a methodological framework in the process of formulating Islamic law. Its role is not merely theoretical, but also serves as a dynamic foundation of legal reasoning in responding to social and intellectual developments. This article aims to examine ushul fiqh as a dynamic foundation of Islamic legal thought using a conceptual and descriptive-analytical approach. The discussion focuses on the definition of ushul fiqh, its function and urgency in Islamic law, and its relevance in addressing contemporary issues. The study concludes that ushul fiqh possesses methodological flexibility that enables Islamic law to remain contextual while preserving its fundamental values. Ushul fiqh merupakan disiplin ilmu yang berfungsi sebagai kerangka metodologis dalam proses penetapan hukum Islam. Keberadaannya tidak hanya berperan sebagai kumpulan teori, tetapi juga sebagai landasan berpikir yang bersifat dinamis dalam merespons perkembangan zaman. Artikel ini bertujuan untuk mengkaji peran ushul fiqh sebagai landasan dinamis pemikiran hukum Islam dengan menggunakan pendekatan konseptual dan deskriptif-analitis. Pembahasan difokuskan pada pengertian ushul fiqh, fungsi dan urgensinya dalam hukum Islam, serta relevansinya dalam menghadapi problematika kontemporer. Hasil kajian menunjukkan bahwa ushul fiqh memiliki fleksibilitas metodologis yang memungkinkan hukum Islam tetap kontekstual tanpa kehilangan nilai-nilai dasarnya.